2014
DOI: 10.1038/sj.ebd.6401026
|View full text |Cite
|
Sign up to set email alerts
|

Amalgam or composite fillings — which material lasts longer?

Abstract: There is low-quality evidence to suggest that resin composites lead to higher failure rates and risk of secondary caries than amalgam restorations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…29 In contrast, factors such as adhesive technique, adhesive system, polymerization shrinkage, type of dental substrate (enamel / dentin) and the quality of the hybrid layer can act critically towards adhesive failure in the composites, thus increasing the risk of recurrent caries. With regard to fractures, there was no statistically significant difference between the two materials (P = 0.46), which was also observed in another study, 26 indicating a lower sensitivity of the posterior restorations to fracture when compared to recurrent caries. M a n u s c r i p t 9 In summary, the meta-analysis based on the results of the eight studies included showed a higher longevity of the amalgam restorations compared to composite resin restorations.…”
Section: Page 8 Of 24supporting
confidence: 71%
“…29 In contrast, factors such as adhesive technique, adhesive system, polymerization shrinkage, type of dental substrate (enamel / dentin) and the quality of the hybrid layer can act critically towards adhesive failure in the composites, thus increasing the risk of recurrent caries. With regard to fractures, there was no statistically significant difference between the two materials (P = 0.46), which was also observed in another study, 26 indicating a lower sensitivity of the posterior restorations to fracture when compared to recurrent caries. M a n u s c r i p t 9 In summary, the meta-analysis based on the results of the eight studies included showed a higher longevity of the amalgam restorations compared to composite resin restorations.…”
Section: Page 8 Of 24supporting
confidence: 71%
“…If dental amalgam were no longer available as a restorative material, populations with high caries rates could therefore be disadvantaged. 16 The most recent data records dental amalgam being used by 85.8% of dentists in South Africa. 19 In these situations, extending the longevity of defective dental amalgam restorations with a repair or refurbishment may be an excellent alternative for increasing the longevity of the restoration and ultimately, the tooth.…”
Section: S Naidoomentioning
confidence: 99%
“…However, a Cochrane Review published in 2014 concluded that the failure rate for composite restorations was twice that of amalgam restorations. 16 Despite this, increasing concern over aesthetics, the recent Minamata Convention on Mercury 17 and advances in adhesive dentistry have globally decreased the acceptance of dental amalgam among dentists and patients alike. 18 saDJ september 2017, Vol 72 no 8 p366 -p371 rZ adam 1…”
Section: Introductionmentioning
confidence: 99%
“…Currently, direct composite restorations are only indicated when patients have excellent oral hygiene, due to the greater adherence of plaque that occurs on this type of materials [29] . The higher probability of having more plaque adhesion on resin-based materials than in amalgam, calls for even more detailed instructions that have to be given to the patient, regarding oral hygiene, when these materials are selected [30] .Thus, a flawless restoration placement and, simultaneously, appropriate oral hygiene, have a positive effect increasing the longevity of restorations and decreasing their need of replacement [31,32] .…”
Section: Discussionmentioning
confidence: 99%